A Review of the Past and the Present Cases of Human African Trypanosomiasis in South Sudan - Yatta S. Lukou; Erneo B. Ochi (Research Aspects in Biological Science Vol. 8, 2022)
Human African Trypanosomiasis, also known as sleeping sickness, is a lethal parasitic disease transmitted by tsetse flies. It was first reported in Southern Sudan, in the early 1900s and most likely introduced into Southern Sudan during the colonial era. South Sudan seceded from Sudan in 2011. The Country infrastructures were destroyed during the war and South Sudan is now rebuilding its health infrastructure. The World Health Organization set a road map for elimination of Human African Trypanosomiasis in all the endemic countries. South Sudan’s National Ministry of Health and its international partners consecrate a lot of efforts to control and eliminate Human African Trypanosomiasis, but cases continue to be reported. The aim of this paper is to review cases of Human African Trypanosomiasis, shading light on the past and the present cases and elucidating causes that might have led to persistence of the disease in some known foci in the country. Data on Human African Trypanosomiasis cases were gathered from a number of pertinent sources, including disease reports from the World Health Organization (WHO) from 1956 to 2018. HAT events were thus classified into the following four historical eras: The First Civil War (1955-1972); the post-Addis Ababa Accord (1973-1982); the Second Civil War (1983-2004); and the post-Comprehensive Peace Agreement (CPA) as of 2005- 2018. The highest HAT cases of 16,539 (52.3%) occurred during the Second Civil War, followed by 7,708 (24.37%) cases in post Addis Ababa Accord; 5,164 (16.33%) cases in post-CPA, and 2,215 (7.0%) cases during the First Civil War totaling ton 31,626 cases. Low HAT prevalence in the 1950s and 1960s might be due to deployment of effective control measures. HAT high prevalence rate during the Second Civil War could be ascribed to political disruptions, instability and civil unrest. At present, no HAT cases reported from Akobo and Pachalla foci in Jonglei State of South Sudan. All HAT past foci of South Sudan are still active with exception of Raga in Western Bahr El-Ghazal State.